Patterns of afferent input to the caudal and rostral areas of the dorsal premotor cortex (6DC and 6DR) in the marmoset monkey. Issue 16 (16th June 2014) - Burman, Kathleen J.; Bakola, Sophia; Richardson, Karyn E.; Reser, David H.; Rosa, Marcello G.P.
ABSTRACT Corticocortical projections to the caudal and rostral areas of dorsal premotor cortex (6DC and 6DR, also known as F2 and F7) were studied in the marmoset monkey. Both areas received their main thalamic inputs from the ventral anterior and ventral lateral complexes, and received dense projections from the medial premotor cortex. However, there were marked differences in their connections with other cortical areas. While 6DR received consistent inputs from prefrontal cortex, area 6DC received few such connections. Conversely, 6DC, but not 6DR, received major projections from the primary motor and somatosensory areas. Projections from the anterior cingulate cortex preferentially targeted 6DC, while the posterior cingulate and adjacent medial wall areas preferentially targeted 6DR. Projections from the medial parietal area PE to 6DC were particularly dense, while intraparietal areas (especially the putative homolog of LIP) were more strongly labeled after 6DR injections. Finally, 6DC and 6DR were distinct in terms of inputs from the ventral parietal cortex: projections to 6DR originated preferentially from caudal areas (PG and OPt), while 6DC received input primarily from rostral areas (PF and PFG). Differences in connections suggest that area 6DR includes rostral and caudal subdivisions, with the former also involved in oculomotor control. These results suggest that area 6DC is more directly involved in the preparation and execution of motor acts, while area 6DR integrates sensory and internally driven inputs for the planning of goal‐directed actions. They also provide strong evidence of a homologous organization of the dorsal premotor cortex in New and Old World monkeys. J. Comp. Neurol. 522:3683–3716, 2014. © 2014 Wiley Periodicals, Inc.